The Effect of Inventory Management Efficiency, Receivables Management, and Asset Turnover on Profitability in Retail Companies Listed on the IDX for the 2020-2024 Period - Sri Nanda Hikmatulloh; Erwin Budianto (Interdisciplinary Social Studies, 2026)
The Indonesian retail sector faces profitability pressures from sales–profit margin imbalances, weak purchasing power, and working capital inefficiencies, yet empirical evidence on their simultaneous effects in the post-pandemic period remains scarce. This research analyzes the effect of inventory management efficiency, receivables management, and asset turnover on the profitability of retail companies listed on the Indonesia Stock Exchange for the 2020–2024 period. Profitability is proxied by Return on Assets (ROA), while the independent variables used are Inventory Turnover (ITO), Receivable Turnover (RTO), and Total Asset Turnover (TATO). The study employed an associative quantitative approach with secondary data from annual financial statements of 7 retail companies (35 observations), analyzed using multiple linear regression assisted by IBM SPSS. The results showed that ITO had a negative and insignificant effect on ROA (sig. 0.193), RTO had a positive and significant effect on ROA (sig. 0.001), while TATO had a positive but insignificant effect (sig. 0.962). Simultaneously, the three variables had a significant effect on ROA (sig. 0.006) with a determination coefficient value (R²) of 0.325, meaning that 32.5% of the variation in profitability can be explained by the model. This indicates that the effectiveness of receivables management is the dominant factor in increasing the profitability of retail companies